IMPROVING STUDENTS ENGLISH WORD SPELLING ABILITY BY USING WORD OLYMPICS GAME - NIM F12409084, S U R T I N I; Rosnija, Eni; Wijaya, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: This research is conducted to investigate how well Word Olympics Game improves the students English word spelling ability at the fifth grade-A students of SD Bruder Nusa Indah Pontianak. The method used is a classroom action research in which the researcher taught English word spelling through Word Olympics Game to improve their word spelling ability. This technique gave students opportunities to write the English words repeatedly, so, they had interesting experiences and accustomed to English words. Researcher used field notes, written test and the interpretation of students score to collect data. The results showed that students scores were getting better at every cycle where the average score of the tests were increased significantly from 56.3 in the first, 67.0 in the second and 78.6 in the third cycle. That proved that the action hypothesis of this research was accepted. The use of Word Olympics Game was pretty well improves the students word spelling ability. Key Words: WOG, Students Word Spelling Ability Abstrak: Penelitian ini bertujuan untuk mengetahui kebaikan Word Olympics Game dalam meningkatkan kemampuan menulis ejaan kata dalam bahasa Inggris pada SD Bruder Nusa Indah kelas V- A Pontianak. Metode yang digunakan adalah Penelitian Tindakan Kelas dimana peneliti mengajarkan ejaan kata bahasa Inggris menggunakan WOG untuk meningkatkan kemampuan mereka dalam menulis ejaan kata. Teknik ini memberikan kesempatan kepada siswa untuk menulis ejaan kata bahasa Inggris secara berulang-ulang sehingga mereka mendapat pengalaman yang menarik dan terbiasa dengan ejaan kata dalam bahasa Inggris. Dalam pengumpulan data peneliti menggunakan catatan lapangan, tes tertulis dan menginterpretasikan hasil tes mereka. Hasilnya menunjukkan bahwa hasil tes siswa semakin membaik di setiap minggunya dimana nilai rata-rata nilainya meningkat secara signifikan dari 56.3 di siklus pertama, 67.0 di siklus kedua dan 78.6 di siklus ketiga. Itu membuktikan bahwa hipotesis tindakan penelitian ini diterima. Penggunaan WOG cukup baik dalam meningkatkan kemampuan menulis ejaan kata bahasa Inggris siswa Kata Kunci: WOG, kemampuan mengeja kata bahasa Inggris